The leucaena psyllid in Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
As far back as October 1989 in the Newslines of Spore 23 we wrote of the danger posed to Africa by the leucaena psyllid (Heteropsylla cubana). Kenya now reports infestations of the psyllid which was originally in the coastal area but now appears to...